The list : a novel - Adegoke, Yomi (William Morrow, 2023)
"Ola Olajide, a celebrated journalist at Womxxxn magazine, is set to marry the love of her life in one month's time. Young, beautiful, and successful--she and her fiancé Michael are considered the "couple goals" of their social network and seem to have it all. That is, until one morning when they both wake up to the same message: "Oh my god, have you seen The List?" It began as a crowdsourced collection of names and somehow morphed into an anonymous account posting allegations on social media. Ola would usually be the first to support such a list--she'd retweet it, call for the men to be fired, write article after article. Except this time, Michael's name is on it. Compulsively readable, wildly entertaining, and filled with sharp social insight, The List is a piercing and dazzlingly clear-sighted debut about secrets, lies, and the internet. Perfect for fans of Such a Fun Age, Luster, and My Dark Vanessa, this is a searing portrait of these modern times and our morally complicated online culture" --